(untitled) (New York, NY., 2003)
This study gives valuable insights into the complex interaction between social security law and private tort law. It is based on reports from eleven European countries, namely Austria, Belgium, England, France, Germany, Greece, Italy, the Netherlands, Switzerland, Spain and Sweden. Leading experts from these jurisdictions provide a concentrated overview of the social security systems in their countries and identify the important differences between social security and tort law compensation in the field of personal injuries. The interrelation between both branches of law is reviewed with respect, e.g., to accidents in the occupational sphere, contributory negligence, recourse actions and bulk agreements between public and private insurance schemes. An extensive comparative report highlights the European perspective and the general interplay between social security law and tort law. The legal perspective is supplemented by an economical analysis of both systems.
Keywords: Social security,Torts; Law and legislation,Cases; Austrian